Children and adolescents with non-Hodgkin lymphoma in Brazil: A national survey identifies the challenges encountered and documents the diversity of care - Costa, Ana Rosa S. [UNESP]; Costa, Juliana T.; Breviglieri, Carla Nolasco Monteiro; Melgares, Lucélia M.P.; Godinho, Patrick R.; Metzger, Monika L. (Elsevier, 2022)
Introduction: Brazil has many inequities in the healthcare provided nationwide. Therefore, in order to access challenges in treatment, available resources and current practices, to identify barriers in delivering a good quality of care among Brazilian centers treating children and adolescents with Non-Hodgkin Lymphoma (NHL) and to generate a future prospective guideline, a customized online survey was distributed to pediatric hematologists and oncologists across the country. Results: A total of 97 surveys were completed (35% response rate), from 47 cities in all Brazilian regions and 79 units of care, with a median of 1 answer by the center (range 1 - 5). Most respondents work at an institution supported exclusively by public/philanthropic resources (58%), with an average of 5 to 9 new cases/year (49%), and 41% have 4 to 6 oncologists/centers. Additionally, 22% have no easy access to the intensive care unit, 26% have no access to Rasburicase, 28% have no access to Rituximabe as front-line therapy and 41% have unreliable methotrexate monitoring levels. Those differences cannot be explained thoroughly by regional wealth variances, nor by the financing model. Regarding the pathology service, 70% consider having reasonable quality assistance, but the timeframe to deliver diagnosis is satisfactory to 46%. There is no uniform management of care, with the current guideline from the Sociedade Brasileira de Oncologia Pediátrica being adopted by 54 to 59%, depending on the NHL subtype. Conclusion: This study provides insights into the heterogeneity of care among Brazilian centers. Recognizing those diversities will support the design of effective strategies and collaboration nationwide.
Keywords: Brazil; Lymphoma; Non-Hodgkin